Evaluación de la incidencia de la satisfacción en el desempeño laboral de los empleados de la ESPAM MFL-EP - Cano Montesdeoca, María Vanessa (2022)
The purpose of this study was to determine the incidence of job satisfaction in the performance of officials of a public company. The purpose of the ESPAM MFL-EP company is to generate income through self-managed activities. It is also in charge of administering human and financial resources effectively and efficiently. In the development of the investigation, it was found that this public entity had not applied performance evaluations, they were unaware of the compliance rates, and the levels of satisfaction perceived by the working staff. Bibliographical research was carried out to summarize the indicators of performance and job satisfaction to be evaluated. Using the Delphi method, a group of professionals was selected who identified and defined the most important indicators, thus building the evaluation tools with the support of Torgerson's mathematical model. Subsequently, a user satisfaction survey was applied. The performance and job satisfaction analysis of each employee were carried out with the information and data collected. As a result, levels of performance were assessed to a medium degree and a high rate of perception of satisfaction was shown. This information made it possible to determine the relationship between both variables, reflecting a Correlation Coefficient of 0.136, which is moderately positive. That is, the performance variables must display high levels. Likewise, the satisfaction manifested by ESPAM MFL-EP officials is also high. Finally, given the results, the critical performance points were defined and a proposal for an action plan was prepared, which was duly communicated.